2022
DOI: 10.3390/biomedicines10123279
|View full text |Cite
|
Sign up to set email alerts
|

Transposons Acting as Competitive Endogenous RNAs: In-Silico Evidence from Datasets Characterised by L1 Overexpression

Abstract: LINE L1 are transposable elements that can replicate within the genome by passing through RNA intermediates. The vast majority of these element copies in the human genome are inactive and just between 100 and 150 copies are still able to mobilize. During evolution, they could have been positively selected for beneficial cellular functions. Nonetheless, L1 deregulation can be detrimental to the cell, causing diseases such as cancer. The activity of miRNAs represents a fundamental mechanism for controlling trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…It should be added that the reduction in pericyte vascular coverage observed in the heart or lungs of patients with COVID-19 indicated that SARS-CoV-2 may affect the microvasculature by targeting pericytes. It has been noted that an increase in adverse cardiovascular events, which often affect young and athletic people as we mentioned earlier, could be an event due to either the greater accumulation of Ang II or to the higher level of active circulating SCs much more present in younger individuals and those who practice sport [96][97][98][99][100].…”
Section: Proposed Model Of Different Spike Protein Syndrome's Patholo...mentioning
confidence: 66%
See 2 more Smart Citations
“…It should be added that the reduction in pericyte vascular coverage observed in the heart or lungs of patients with COVID-19 indicated that SARS-CoV-2 may affect the microvasculature by targeting pericytes. It has been noted that an increase in adverse cardiovascular events, which often affect young and athletic people as we mentioned earlier, could be an event due to either the greater accumulation of Ang II or to the higher level of active circulating SCs much more present in younger individuals and those who practice sport [96][97][98][99][100].…”
Section: Proposed Model Of Different Spike Protein Syndrome's Patholo...mentioning
confidence: 66%
“…The inflammatory process can spread up to the fiber tracts located in the dorsal roots reaching the ganglion neurons that from there tend to influence neurons in the spinal cord, reaching the sympathetic efferent neurons. The direct involvement of stem cells is therefore assumed, derived infected mature and progenitor neuro cells may also contribute to the disorders of sympathetic afferent neurons that are associated with multiple districts such as heart, esophagus and bronchi through: i), the affection of vagal afferent axons that are associated with myocardial receptors, which ascend in the vagal nerves up to the node ganglion reaching the nucleus of the tractus solitarius and interneurons; and, ii) these interneurons will in turn affect the vagus and sympathetic preganglionic efferent nerves in the bulbospinal tracts [97][98][99][100].…”
Section: Proposed Model Of Different Spike Protein Syndrome's Patholo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Esposito et al [28] studied a possible new function of transposons (TEs), which are mobile genetic elements that can move around the genome and sometimes affect the expression of nearby genes. TEs, depending on where they jump, can insert functional domains such as miRNA binding sites transforming transcripts in miRNA sponges (see reference in the paper).…”
Section: "Non-canonical" Mirnas and Mirna Regulationmentioning
confidence: 99%
“…ERVs can modulate gene expression, contribute to genetic variation and drive evolution. They have also been co-opted by the host for beneficial roles in some instances [21,22].…”
Section: Introductionmentioning
confidence: 99%